Developing English Learning Material with Islamic Context for Pre-Service Mathematics Teachers - Ulpah, Maria; Muflihah, Muflihah; Hidayati, Uli (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Few English materials integrate Islamic values for mathematics teacher education. This study aimed to develop an Islamic context-based English learning material for pre-service mathematics teachers to address the need for integrating language proficiency with religious values. Using R&D approach with the 4D model, the study involved needs analysis, expert validation, limited trials, and effectiveness testing. The material covered mathematics topics such as symbols and operations, plane and solid geometry enriched with Islamic contexts including Qur’anic references and the contributions of Muslim mathematicians. This is among the first to embed Qur’anic references and Muslim mathematicians in English for Mathematics materials. Validation by three domain experts (mathematics, English, and Islamic education) resulted in high scores of 4.12 (82.3%), 4.59 (91.8%), and 4.06 (81.2%), respectively, indicating strong validity. Student assessments further supported its validity with an average score of 4.41 (88.1%). Effectiveness testing using a quasi-experimental design revealed a statistically significant improvement in the experimental group’s English proficiency, with an N-Gain score of 0.57 compared to 0.39 in the control group (p < 0.05). These findings confirm that the developed material is valid, practical, and effective for improving English skills. However, the study was limited to only two classes in a single institution.